Conjugated Polymers: Conjugated Donor–Acceptor Terpolymers Toward High‐Efficiency Polymer Solar Cells (Adv. Mater. 22/2019). Issue 22 (27th May 2019) - Dang, Dongfeng; Yu, Donghong; Wang, Ergang
Abstract : In article number1807019, Ergang Wang and co‐workers review the recent progress of conjugated donor–acceptor (D–A) terpolymers for efficient polymer solar cells. Compared to D–A alternating copolymers, such terpolymers can give a facile method to not only improve their light absorption, but also fine‐tune their energy levels and interchain packing synergistically. Thereby, they highlight the great potential of terpolymers for efficient polymer solar cells.